Systemic aspects of ensuring the efficiency of sitilogistics - Dobrovolskа Anna; Dobrovolskiy, Oleksandr; Volynets, Lyudmila; Sakhno, Serhii (Management and Entrepreneurship: Trends of Development, 2026)
The article presents a systematic analysis of the key challenges of the international road freight market, which determine the current conditions for the functioning of logistics providers. It is substantiated that the increased complexity of organizing international road freight causes the emergence of multifactorial problems that affect the effectiveness of logistics providers and reduce the stability of cargo delivery processes. Particular attention is paid to the study of destabilizing factors associated with vehicle downtime, which lead to a decrease in the efficiency of freight forwarding operations and negatively affect the timeliness and reliability of cargo delivery within logistics supply chains. The purpose of the study is to analyze the key challenges in the international road freight market that affect the functioning of logistics providers, as well as to substantiate the directions for minimizing the negative impact of vehicle downtime on the processes of international road freight transportation in order to increase the operational efficiency of logistics providers. The study uses the method of a systems approach, which allowed considering international road freight transportation as an integral logistics system with interconnected elements, the methods of structural and functional analysis, comparison and generalization allow determining the impact of vehicle downtime on the efficiency of logistics providers, and also uses elements of the process approach and methods for optimizing management decisions in the field of transport logistics in order to substantiate organizational and logistical measures to increase the efficiency of logistics providers in conditions of vehicle downtime. It has been determined that the comprehensive application of organizational and logistical measures in road freight transportation, in particular the conclusion of application contracts between transportation participants with clear regulation of transportation conditions, detailed planning, coordination and control of all stages of the logistics process by logistics providers, as well as the development of alternative delivery routes, ensures increased efficiency in material flow management. The implementation of organizational and logistical measures contributes to the increase in the adaptability of logistics systems, their increased resistance to external influences and the strengthening of the competitive positions of companies in the logistics services market. At the same time, improving the organization of road freight transportation is a necessary condition for ensuring high quality logistics services. The implementation of organizational and logistical measures in the context of minimizing downtime increases the efficiency and reliability of logistics processes and can be effectively used in the activities of logistics providers. JEL Classification: R41, L91.